Innovation in identifying metabolites from complex metabolome—Highlights of recent analytical platforms and protocols - Qiu, Shi; Guo, Sifan; Yang, Qiang; Xie, Yiqiang; Tang, Songqi; Zhang, Aihua (Frontiers in Chemistry, 2023)
Metabolites are closely intertwined genotypes that can provide clear information about the final phenotype. The high-throughput analysis platform used to identify candidate metabolites and describe their contributions can help to quickly detect metabolic characteristics from large spectral data, which may lead to peak data preprocessing, statistical analysis and functional interpretation. Developing a comprehensive strategy for discovering and verifying bioactive metabolites can provide a large number of new functional biomarkers, and then more closely reveal their functional changes, which has relevant biological significance for disease diagnosis and prognosis treatment.